PERAN DANA ZAKAT DALAM PROGRAM RIAU CERDAS TERHADAP TINGKAT PENGANGGURAN DI PROVINSI RIAU (Studi Kasus Baznas Provinsi Riau) - , Supriani Sidabalok, Meisyalerita Vivialyn Salsabila ,Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The research aims to determine the role of zakat funds in the Smart Riau program on  the unemployment  rate in  Riau  Province.  In  this study using  a  saturated sample where the entire population is a sample with a total of 47 respondents who are college level mustahik Riau Smart scholarships. The data used in this study are primary and secondary data. Primary data was obtained from distributing questionnaires to respondents while secondary data was obtained from Baznas Riau  Province.  Data  collection  techniques  using  a  questionnaire.  The  data analysis method used is multiple linear regression analysis using Zakat Variables as  (X1),  Grade  Point  Average  (X2)  and  Long  Waiting  for  the  first  Job  as indicators of unemployment (Y). The results of multiple linear regression analysis show that the zakat variable and the cumulative GPA simultaneously have a positive effect on the unemployment rate in Riau Province. This can be proven from the results of the calculated F value of 33.241 > F table 4.06 with a significance value of 0.000 <0.05. The results of the partial test of the zakat variable (X1) on unemployment (Y) have a negative and significant effect. This is evidenced by the obtained t value -3.128 <t table 2.015 and a significant value of 0.003 <0.05. Meanwhile, the partial test results for the Cumulative Grade Point Average (X2) variable on unemployment (Y) have a negative and significant effect. With the results obtained, the t count is -7.898 <t table 2.0153 and a significant value of 0.000 <0.05 Keywords: Smart Riau, Unemployment, Zakat